Validation of spiked postmortem blood samples from cornea donors on the abbott ARCHITECT and m2000 systems for viral infections - Schmack, Ingo; Ballikaya, Seda; Erber, Brigitte; Burkhardt, Ulrich; Auffarth, Gerd U.; Schnitzler, Paul (Transfusion medicine and hemotherapy, 2020)
Background: Transplantation of human corneal tissue is associated with the potential risk of transmittance of viral infections. In accordance with European directives and federal laws, in Germany each tissue donor has to be tested for infectious diseases such as hepatitis B and C virus (HBV and HCV) and human immunodeficiency virus (HIV) infection. However, most of the currently available CE-marked serologic and nucleic acid screening systems are only validated for antemortem blood. Methods: Twenty related and paired ante- and postmortem blood samples from cornea donors were obtained and subsequently analyzed for hepatitis B surface antigen (HBsAg), hepatitis B antibody (anti-HBc), anti-HCV, HCV RNA, anti-HIV-1/2, and HIV p24 Ag using Abbott test systems. The sera were also spiked with reference materials in concentrations giving low and high positivity for HBV, HCV, and HIV markers. Results: The spiked ante- and postmortem sera from related donors showed similar results for HBsAg, anti-HBc, anti-HCV, HCV RNA, anti-HIV, and HIV p24 Ag, indicating a high stability of viral markers in cadaveric specimens. Three cornea donors had a medical history of HBV infection and revealed anti-HBc at similar levels in the ante- and postmortem sera. In addition, there was a single postmortem sample demonstrating a weak signal of anti-HIV-1 and HIV-1 p24 Ag. False-positive or false-negative results were not detected. The results obtained with the Abbott ARCHITECT analyzer and Abbott RealTime HCV PCR showed no significant differences. Conclusion: The analyzed screening assays are suitable for the detection of infectious markers of HBV, HCV, and HIV at similar levels in spiked ante- and postmortem sera from cornea donors.